Attitudes toward lying in primary school students with different levels of moral development: a gender perspective in the context of the International Day of Women and Girls in Science (Universal International Scientific Journal, 2026)
This article is devoted to an empirical study of attitudes toward lying in primary school-aged children (ages 7–10) depending on their level of moral development. Using a sample of 40 students (21 girls and 19 boys), it was found that a high level of moral development correlates with a consciously negative, empathic attitude toward lying and a focus on internal moral norms. A low level is associated with the instrumental use of lying as a means of avoiding punishment or adapting. The study's novelty lies in its detailed gender analysis, the integration of the results into the context of the International Day of Women and Girls in Science (February 11), and its reliance on the work of Associate Professor A. I. Yanchiy in developmental psychology and moral education. The data obtained allow us to offer practical recommendations for fostering honesty in elementary school, with a particular focus on supporting girls in developing ethical and scientific thinking.
Keywords: primary school students, moral development, attitude towards lying, gender differences, ethical education, women in science, A. I. Yanchiy.